La traque policière des étranger·es à la frontière franco-italienne (Hautes-Alpes) comme « maintien de l’ordre » social et racial - Sarah Bachellerie (Revue de Géographie Alpine)
In the town of Briançon (Hautes-Alpes), on the French side of the French-Italian border, the border police (PAF) controls for those who have crossed the border illegally by operating on a discretionary basis. Mobile police practices include tracking down racialised people across the mountains. These practices expose illegal migrants to dangers inherent in the high-mountain environment and are part of a continuum of police and administrative violence committed against them. Migration control in the Briançon area demonstrates how the mountains can be integrated into power strategies that reinforce the dominance of certain social groups. It also shows that borders today, which facilitate the mobility of “legitimate” foreign populations and hinder that of “undesirable” foreign populations, function by identifying individuals and differentiating them on the basis of race and class. The persistence of “police hunts for illegal humans” (Chamayou, 2010) as a control technology helps us, on the whole, to understand how migration control on France’s borders forms part of a “colonial present” (Gregory, 2004).